Implementation of Teacher Training: Providing Specialized Training for Teachers to Handle Multilingual Classrooms Effectively - Teguh Satria Amin; Berlin Sibarani; Siti Aisah Ginting; Rahmad Husein; Rini Ekayati (PT Inovasi Pratama Internasional, 2024)
The rapid globalization and increased migration have led to a significant rise in multilingual classrooms. This dynamic presents unique challenges and opportunities in educational settings, necessitating specialized training for teachers. The increasing diversity in classrooms requires teachers to have the necessary skills and knowledge to cater to the needs of multilingual students. The findings and discussions highlight the benefits of specialized training for teachers and its impact on student outcomes. This article examines the implementation of teacher training programs focused on equipping educators with the skills and strategies needed to effectively manage and teach in multilingual environments. The article reviews literature on the challenges faced by teachers in multilingual classrooms and the impact of specialized training on teacher effectiveness. The method section outlines the various training programmes available for teachers and their effectiveness. Drawing on data from recent studies, statistics, and case examples, the paper examines the effectiveness of these training programmes and offers recommendations for future practice. The findings suggest that specialised training significantly improves teachers' ability to manage multilingual classrooms, promotes inclusive education, and enhances student outcomes. The conclusion emphasises the need for ongoing professional development for teachers in multilingual settings.